Makna Simbolik Perahu Paledang pada Komunitas Pemburu Paus dan Penenun di Desa Lamalera, Pulau Lembata - Lerrick, Jesica Herlin; Yuwono, J. Susetyo Edy (JANUS, 2025)
The traditional Paledang boat holds a central position in the lives of the Lamalera community on Lembata Island. The profound meaning of this vessel is not only evident in maritime life, but is also visually woven into the motifs of local ikat weaving. This study aims to understand how the Lamalera community interprets the form of the Paledang boat, both as a whaling vessel and as a motif in the woven textiles they produce. Using an ethnoarchaeological approach, this research analyzes two cultural objects through five variables: construction techniques, temporal and spatial contexts, traditional organization, ceremonial and ritual practices, and the utilization of the Paledang boat and its motif in Lamalera ikat weaving. The findings indicate that the Paledang is not merely a tool for whaling, but also represents identity, courage, and a spiritual connection with the sea. Meanwhile, the Paledang motif in Lamalera ikat weaving is not only an aesthetic decoration, but also carries important social and symbolic meanings, particularly in relation to women’s status and exchange within the socio-economic networks of the Lamalera community. === Perahu Paledang memiliki kedudukan sentral bagi masyarakat Lamalera, Pulau Lembata. Kuatnya makna perahu ini tidak hanya hidup di lautan, tetapi juga terekam secara visual dalam motif kain tenun ikat lokal. Penelitian ini bertujuan untuk memahami pemaknaan masyarakat Lamalera terhadap bentuk perahu Paledang, baik sebagai sarana perburuan paus maupun sebagai motif kain tenun yang mereka produksi. Dengan pendekatan etnoarkeologi, penelitian ini menganalisis dua objek budaya melalui lima variabel pengamatan: teknik pembuatan, waktu dan tempat pelaksanaan, organisasi tradisional, upacara dan ritual, serta pemanfaatan perahu Paledang dan motif perahu Paledang pada kain tenun Lamalera. Hasil penelitian menunjukkan luasnya makna perahu Paledang yang bukan sekadar alat berburu paus, melainkan wujud identitas, keberanian, dan hubungan spiritual dengan laut. Di sisi lain, motif Paledang dalam tenun tidak hanya sebagai hiasan estetis, tetapi juga sarat makna sosial dan simbolik, khususnya dalam konteks status perempuan dan pertukaran dalam jaringan sosial-ekonomi masyarakat Lamalera.